Secretory Structure and Histochemistry Tests of Asteraceae Family Members of Medicinal Plants in Walat Mountain Educational Forest - Dorly Dorly; Bimo Adi Wiryo; Ismi Nurfaizah; RR. Syafira Nidyasari (Universitas Sebelas Maret, 2015)
The diversity of Walat Mountain Educational Forest is not only fauna but also very rich of various kinds of flora such as several kinds of medicinal plants. This research was aimed study the variety of secretory structure and histochemistry of three kinds of medicinal plants found in of Walat Mountain Educational Forest. Plant materials used were billy-goat weed (Ageratum conyzoides), balakacida (Mikania cordata), and monyenyen (Erigeron linifolius).The medicinal plant leaves were made into paradermal and transversal sections, then secretory structures were observed, and the histochemistry of terpenoid, alkaloid, phenol and oil compounds was tested. The results of this research on adaxial and abaxial billy-goat weed leaves were found multicellular glandular trichome and peltate type glandular trichome. Besides, oil drops were also found on billy-goat weed palisade tissue. On adaxial and abaxial bakalacida leaves were found multicellular glandular trichome type 1 and type 2, andpeltate type glandular trichome. Moreover on adaxial and abaxial monyenyen leaves were found multicellular glandular trichome type 1 and type 2. The results of histochemical test on billy-goat weed were the multicellular glandular trichome did not contain terpenoid, alkaloid, phenol, and oil compounds, while on peltate type glandular trichome was positive to terpenoid. Both types of multicellular glandular trichomes on balalakacida plant were positive to terpenoid, alkaloid, and oil compounds, except phenol. Whereas peltate type glandular trchome was positive to alkaloid, phenol, and oil compounds, except terpenoid. Histochemical test results on both types of multicellular glandular trichomes of monyenyen plant were positive to terpenoid and oil compounds.Keywords: secretory structure, histochemical tests, glandular trichome